2020
DOI: 10.1016/j.spa.2019.07.006
|View full text |Cite
|
Sign up to set email alerts
|

A reduction principle for the critical values of random spherical harmonics

Abstract: We study here the random fluctuations in the number of critical points with values in an interval I ⊂ R for Gaussian spherical eigenfunctions {f ℓ }, in the high energy regime where ℓ → ∞. We show that these fluctuations are asymptotically equivalent to the centred L 2 -norm of {f ℓ } times the integral of a (simple and fully explicit) function over the interval under consideration. We discuss also the relationships between these results and the asymptotic behaviour of other geometric functionals on the excurs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…This procedure will guarantee that the estimator has minimal variance. Corollary 1 is consistent with recent results on the so‐called Berry's cancelation phenomenon, that is, the fact that the variance of the LK curvatures at level s u reaches a minimum, because of the disappearance of a large number of chaotic terms (see Cammarota & Marinucci, 2020).…”
Section: Estimators Of the Effective Level And Effective Spectral Momentsupporting
confidence: 91%
“…This procedure will guarantee that the estimator has minimal variance. Corollary 1 is consistent with recent results on the so‐called Berry's cancelation phenomenon, that is, the fact that the variance of the LK curvatures at level s u reaches a minimum, because of the disappearance of a large number of chaotic terms (see Cammarota & Marinucci, 2020).…”
Section: Estimators Of the Effective Level And Effective Spectral Momentsupporting
confidence: 91%
“…Let us stress now that one of the main differences w.r.t. the nodal case (1.6) is that, as argued in [4], thanks to (1.11) the boundary length is asymptotically (as → +∞) perfectly correlated (meaning that the squared correlation coefficients ρ(•, •) converge to one) with other geometric functionals, such as the area [15,16] and the Euler-Poincaré characteristic [4] for the excursion regions A u (f ) = {x ∈ S 2 : f (x) ≥ u}; likewise, perfect correlation holds between these functionals and the number of critical points [5] for f (x) in the same excursion region, for any non-zero threshold u = 0. In other words, at high values of , knowledge of any of these quantities for a given sample yields the full information on the behaviour of all the others for the same sample, up to asymptotically negligible terms.…”
Section: Remark 12 (I)mentioning
confidence: 97%
“…Later in [13] it was shown that the critical values above the threshold level satisfy the asymptotic…”
Section: Wiener-chaos Expansions For Random Eigenfunctionsmentioning
confidence: 99%